miRNA-197 and miRNA-223 and cardiovascular death in coronary artery disease patients - Orenes-Piñero, Esteban; Marín, Francisco; Lip, Gregory Y. H. (Annals of Translational Medicine; Vol 4, No 10 (May 25, 2016): Annals of Translational Medicine (Focus on “State of the Art in Diagnostics of the Acute Coronary Syndrome”), 2016)
Coronary artery disease (CAD) is commonly associated with the presence of atheromatous plaques in the coronary arteries. The growth of these plaques may cause arterial stenosis and blockage of the blood flow, leading to cardiac ischemia and clinical symptoms, such as acute coronary syndrome (ACS) or stable angina pectoris (SAP). Due to the high morbidity and mortality rate, CAD has probably the most serious cardiovascular disorder threatening people’s health in Western countries (1).